Etiologia popełniania zabójstw przez kobiety - Gawenda, Adriana (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This article is an attempt to explain the etiology of women’s homicides, in a comprehensive way. It contains a presentation of scientific theories which have a significant impact on the development of the universal principles of the perception of female killers. In addition to scientific theories, it shows factors which have a decisive influence on committing of this type of crime, and a typology of female killers is described, as well as general determinants included in the modus operandi of homicides perpetrated by women. The article is intended to outline the issues related to the understanding of women opting to deprive the other person of their life.
Keywords: etiologia; kobiety; zabójstwa popełniane przez kobiety; zabójstwa